Mindsight : image, dream, meaning - McGinn, Colin, 1950- (Cambridge, Harvard University Press, 2004)
"The guiding thread of this book is the distinction Colin McGinn draws between perception and imagination. Clearly, seeing an object is similar in certain respects to forming a mental image of it, but it is also different. McGinn shows what the differences are, arguing that imagination is a sui generis mental faculty. He goes on to discuss the nature of dreaming and madness, contending that these are primarily imaginative phenomena. In the second half of the book McGinn focuses on what he calls cognitive (as opposed to sensory) imagination, and investigates the role of imagination in logical reasoning, belief formation, the understanding of negation and possibility, and the comprehension of meaning. His overall claim is that imagination pervades our mental life, obeys its own distinctive principles, and merits much more attention."--Jacket
Images and percepts -- The mind's eye -- Imaginative seeing -- The space of imagery -- The picture theory of images -- What are dreams? -- Dream belief -- Delusion -- The imagination of the child -- Cognitive imagination -- Negation -- Meaning -- The Imagination spectrum
Includes bibliographical references (p. [199]-210) and index
Keywords: Imagination (Philosophy)